PEMANFAATAN LIMBAH TONGKOL JAGUNG (Zea mays L.) SEBAGAI ARANG AKTIF DALAM MENURUNKAN KADAR AMONIA, NITRIT DAN NITRAT PADA LIMBAH CAIR INDUSTRI TAHU MENGGUNAKAN TEKNIK CELUP - Azwar Amin; Saibun Sitorus; Bohari Yusuf (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
A research about utilization of waste corncob (Zea may L.) as active charcoal in reduction ammonia, nitrite and nitrate levels on industrial tofu liquid waste using dye technique have been researched. The purpose of this research to know reduction levels of industrial tofu liquid waste from some parameter is ammonia, nitrite and nitrate by using 2 variations is contact time and pH tofu liquid waste. The percentage yield of research to show of reduction ammonia, nitrite and nitrate levels at the optimum contact time 10 minute and the optimum pH 6 that is 51,29%, 31,93% and 58,71%. And then analyzed of data by using ANOVA test to know Fcount influence of the contact time of active charcoal to reduction ammonia, nitrite and nitrate levels on industrial tofu liquid waste that is 2,4891 less than Ftable 3,00. It is stated that is no significant effet on the reduction ammonia, nitrite and nitrate levels of industrial tofu liquid waste by using variation contact time active charcoal. While Fcount influence of optimum pH industrial tofu liquid waste to reduction ammonia, nitrite and nitrate levels on industrial tofu liquid waste that is 5,7168 more than Ftable 2,07. It is stated that is a significant effet on the reduction ammonia, nitrite and nitrate levels of industrial tofu liquid waste by using variation optimum pH industrial tofu liquid waste.